2012
DOI: 10.1016/j.foodchem.2012.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of vanillin/cyclodextrin inclusion complex in electrospun polyvinyl alcohol (PVA) nanowebs: Prolonged shelf-life and high temperature stability of vanillin

Abstract: We produced functional nanowebs, containing vanillin, having prolonged shelf-life and high temperature stability facilitated by cyclodextrin (CD) inclusion complexation. Polyvinyl alcohol (PVA) nanowebs incorporating vanillin/cyclodextrin inclusion complex (vanillin/CD-IC) were produced via electrospinning technique. The vanillin/CD-IC was prepared with three types of CDs; α-CD, β-CD and γ-CD to find out the most favourable CD type for the stabilization of vanillin. PVA/vanillin/CD-IC nanofibres, having fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
1
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(174 citation statements)
references
References 32 publications
9
162
1
2
Order By: Relevance
“…[1,2]. Owing to the room temperature and ambient process conditions that provide protection for the bioactive compounds in electrospun nanofibers, electrospinning is used for production of functional nanofibers containing active agents like antioxidants [3,4], flavors/fragrances [5,6] and antibacterial agents [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2]. Owing to the room temperature and ambient process conditions that provide protection for the bioactive compounds in electrospun nanofibers, electrospinning is used for production of functional nanofibers containing active agents like antioxidants [3,4], flavors/fragrances [5,6] and antibacterial agents [7].…”
Section: Introductionmentioning
confidence: 99%
“…PVA as a nanofiber matrix was chosen since PVA is a suitable polymer type for food packaging applications shown in the literature by incorporating different molecules or bacteria into PVA films [30] and fibers [5,31] due to its high tensile strength, flexibility, high oxygen and barrier properties. Free AITC and inclusion complex of AITC with ␤-CD (AITC/␤-CD-IC) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, one of the major factors contributing to an observed increase in the diameters of electrospun fibers is an increase in the viscosity of the spinning solution. 28,33 The presence of foreign substances (i.e., AC, HPβCD, and AC/ HPβCD, in this case) would cause the viscosities of the AC-, HPβCD-, and AC/HPβCD-containing CA solutions to increase from that of the neat CA solution. As a result, larger diameters from those of the neat CA fibers were observed.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36] The absence or the presence of the melting point of organic compounds in their free or complex form could be used to confirm the formation of the inclusion complex within fiber mats. 33 Figure 2 shows that pure AC powder exhibited a broad endothermic peak over a temperature range of 40 to 160 o C, associating with the loss of moisture during the heating process, and a melting peak at about 248 o C, corresponding to the melting point of pure AC. The incorporation of AC within the CA fibers (i.e., AC 10 fibers) shows the peak of moisture loss between 40 and 130 o C and two additional endothermic peaks at 218 and 224 o C. While the latter is clearly correspondent to the melting of the CA matrix (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, during encapsulation of bioactive compounds (antioxidants, antimicrobials, probiotics and flavors) these are introduced into a matrix or wall system (edible coating) to prevent their loss; by creating a solid barrier between the additive and environmental conditions, so it is protected. Kayaci and Uyar (2012) produced functional capsules matrix, containing vanillin, having prolonged shelf-life and high temperature stability facilitated by cyclodextrin inclusion complexation. Milanovic et al (2010) showed that the release of ethyl vanillin from wax matrix occurs under heating proceeds at different temperatures; vanillin evaporation occurs close to 200°C, while matrix degradation starts at 250°C.…”
Section: Edible Coatings As a Stabilizing Matrix For Bioactive Compoundsmentioning
confidence: 99%